2017
DOI: 10.5935/1806-6690.20170033
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian organic sugarcane spirits: Physicochemical and chromatographic profile

Abstract: There has been a growing demand for products from organic agriculture for the food market. Brazil leads the production of sugarcane spirits and produces about 1.6 billion liters/year. New technologies have been sought throughout the supply chain to improve production, and organic raw material has been used in the production of sugar cane for the production of beverages. This study aimed to define the physicochemical and chromatographic profiles of eleven organic sugarcane spirits samples from various Brazilian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Several studies of physical and chemical quality of cachaças from Minas Gerais (Fernandes et al, 2007;Santiago et al, 2015;Barcelos et al, 2007;Vilela et al, 2007), Rio Grande do Sul (Schmidt et al, 2009) and Paraná (Volpe et al, 2013) demonstrate that this is a common parameter in disagreement with the governamental. The cachaças from the states of Maranhão and Paraná had a percentage of non-compliance with legal regulations regarding the content of esters, much higher than in this research, being 15 and 18%, respectively limit (Mendes et al, 2016;Duarte et al, 2017). Research has shown that the value of esters in cachaças obtained by column distillers had more than twice the ester content of cachaças distilled in stills, but it is not influenced by the burning of the cane or the storage barrel (Masson et al, 2007;Volpe et al, 2013).…”
Section: Physical-chemical Qualitycontrasting
confidence: 64%
See 3 more Smart Citations
“…Several studies of physical and chemical quality of cachaças from Minas Gerais (Fernandes et al, 2007;Santiago et al, 2015;Barcelos et al, 2007;Vilela et al, 2007), Rio Grande do Sul (Schmidt et al, 2009) and Paraná (Volpe et al, 2013) demonstrate that this is a common parameter in disagreement with the governamental. The cachaças from the states of Maranhão and Paraná had a percentage of non-compliance with legal regulations regarding the content of esters, much higher than in this research, being 15 and 18%, respectively limit (Mendes et al, 2016;Duarte et al, 2017). Research has shown that the value of esters in cachaças obtained by column distillers had more than twice the ester content of cachaças distilled in stills, but it is not influenced by the burning of the cane or the storage barrel (Masson et al, 2007;Volpe et al, 2013).…”
Section: Physical-chemical Qualitycontrasting
confidence: 64%
“…High values of this higher alcohol may be due to an incorrect separation of the distillate fractions (Schmidt et al, 2009). In research by Penteado & Masini (2009) on cachaças from the states of São Paulo and Minas Gerais, this parameter exceeded the limit in 12.1% of the samples while Duarte et al (2017) did not find any sample with concentration above the limit allowed in research with organic cachaças from the Paraná, Minas Gerais, Bahia and Ceará states. The content of esters in cachaça increases with the practice of aging in wooden barrels and is related to the sensory improvement of cachaça over time, however an excess of this constituent may indicate an incorrect separation of the fractions of the distillate and brings unwanted taste to the drink (Bortoletto et al, 2016;Duarte et al, 2017).…”
Section: Physical-chemical Qualitymentioning
confidence: 79%
See 2 more Smart Citations
“…Bortoletto and Alcarde (2015) determined the chemical composition of 268 Brazilian cachaças and observed that 50% of the samples not meeting the quality standards. Finally, Duarte, Cardoso, Santiago, Machado, & Nelson (2017) evaluated organic cachaças with respect to their physicochemical profile and found that only 26% did not meet the limits required by MAPA.…”
Section: Resultsmentioning
confidence: 99%